ANALISIS FAKTOR-FAKTOR PRODUKSI PADA INDUSTRI SEMEN DI INDONESIA - Ilma Prahmalia Tira (Department of Development Economics, Universitas Sriwijaya, 2012)
This research was aimed at identifying the influence of production factors on cement industry output in Indonesia in the period of 1985-2009. The factors identified included energy, fixed capital, labor and raw and auxiliary materials. This research used the secondary data published in reports of Central Bureau for Statistics dealing with 36310 ISIC code in the period of 1985-1997, and 26411 ISIC code in the period of 1998-2009. The research results show that all variables had a positive influence on the cement output in the period of 1985-2009, except one variable called the fixed capital. The energy, fixed capital, labor, raw and auxiliary materials simultaneously had a significant influence on the output. The R2 obtained was 0,883. It means that all variables play a role in influencing the output as much as 88,3% and the rest of 11,7% could be explained by other factors. The elasticity of energy (0,368 < 1), fixed capital (0,019 < 1), raw and auxiliary materials (0,597 < 1) fell in the rational stage meaning the addition of each variables was not proportionate to the output, ceteris paribus. The elasticity of labor was 1,215 > 1 meaning the labor could be encouraged to produce the output more, ceteris paribus. Return to the scale of the cement industry in the period of 1985-2009 was 2,199. This means that there was an increase of one percent for each production factor together willÂ increase production by 2,199Â percent. The efficiency of the cement industry in the period of 1985-2000 was less than one meaning that the industry did not make use of its input efficiently. In the period 2001-2009, the efficiency of the industry was more than one meaning that the industry made use of the input efficiently. Keywords: production, elasticity, return to scale, efficiency, cement industry